2020
DOI: 10.1021/acs.jafc.0c01169
|View full text |Cite
|
Sign up to set email alerts
|

Improving Flavonoid Metabolism in Blackberry Leaves and Plant Fitness by Using the Bioeffector Pseudomonas fluorescens N 21.4 and Its Metabolic Elicitors: A Biotechnological Approach for a More Sustainable Crop

Abstract: Beneficial rhizobacterium Pseudomonas fluorescens N 21.4 and its metabolic elicitors inoculated to cultivars of blackberry (Rubus spp. Var. Loch Ness) reinforced the plants’ immune system and improved their fitness by increasing photosynthesis, decreasing oxidative stress, and activating pathogenesis-related proteins. They also triggered the leaves’ flavonoid metabolism, enhancing the accumulation of beneficial phenolic compounds such as kaempferols and quercetin derivatives. The elicitation of leaf secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 55 publications
3
24
0
Order By: Relevance
“…Since the N 21.4 strain had demonstrated an extraordinary ability to influence the physiology of blackberry plants and to elicit the flavonoid secondary metabolism, it was proposed, in the present work, to evaluate the potential of its ME to mimic the capacities of the live strain. A previous study demonstrated the capacity of ME to elicit flavonoid metabolism in blackberry leaves, enhancing the amount of epicatechin, kaempferol, and quercetin derivatives 19 . It was also seen that ME were able to reinforce the blackberry plant's immune system, activating pathogenesis‐related proteins, and to improve plant fitness, reducing oxidative stress and increasing photosynthesis in the leaves 19 .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Since the N 21.4 strain had demonstrated an extraordinary ability to influence the physiology of blackberry plants and to elicit the flavonoid secondary metabolism, it was proposed, in the present work, to evaluate the potential of its ME to mimic the capacities of the live strain. A previous study demonstrated the capacity of ME to elicit flavonoid metabolism in blackberry leaves, enhancing the amount of epicatechin, kaempferol, and quercetin derivatives 19 . It was also seen that ME were able to reinforce the blackberry plant's immune system, activating pathogenesis‐related proteins, and to improve plant fitness, reducing oxidative stress and increasing photosynthesis in the leaves 19 .…”
Section: Introductionmentioning
confidence: 97%
“…A previous study demonstrated the capacity of ME to elicit flavonoid metabolism in blackberry leaves, enhancing the amount of epicatechin, kaempferol, and quercetin derivatives 19 . It was also seen that ME were able to reinforce the blackberry plant's immune system, activating pathogenesis‐related proteins, and to improve plant fitness, reducing oxidative stress and increasing photosynthesis in the leaves 19 . In other plant species, the ME of N 21.4 also elicited secondary metabolism (e.g.…”
Section: Introductionmentioning
confidence: 97%
“…Based on gene expression and protection results, the Gram-negative Serratia rubidaea N 12.34 and the Gram-positive Bacillus cereus N 4.1 were selected to extract their metabolic elicitors. Bacterial elicitors capable of starting defensive immune responses in plants, have been found to be structural molecules, (e.g., flagellin [53]), or metabolic elicitors that are released into the medium [17,45,[54][55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…[ 35 ] and blackberry ( Rubus cv. Loch Ness) has been largely demonstrated [ 36 , 37 , 38 , 39 ]. Its metabolic elicitors have also been demonstrated to induce systemic resistance in A. thaliana [ 18 ] and to elicit flavonoid metabolism in the leaves and in the fruits of cultivars of blackberry [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%